2018
DOI: 10.1002/chem.201800774
|View full text |Cite
|
Sign up to set email alerts
|

Direct Electrochemistry of Bilirubin Oxidase from Magnaporthe orizae on Covalently‐Functionalized MWCNT for the Design of High‐Performance Oxygen‐Reducing Biocathodes

Abstract: Herein, the direct electrochemistry of bilirubin oxidase from Magnaporthe orizae (MoBOD) was studied on CNTs functionalized by electrografting several types of diazonium salts. The functionalization induces favorable or unfavorable orientation of MoBOD, the latter being compared to the well-known BOD from Myrothecium verrucaria (MvBOD). On the same nanostructured electrodes, MoBOD can surpass MvBOD in terms of both current densities and minimal overpotentials. Added to the fact that MoBOD is also highly active… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 30 publications
2
23
0
Order By: Relevance
“…For the first scan ( Figure 1A, black line) the voltammogram on the forward sweep is characterized by two hysteresis observed at~0.40 V and~0.1 V vs SCE, indicating an activation step at low potentials for the ORR. During the second scan the onset for O 2 reduction occurs at~0.5 V. The hysteresis obtained during the first scan suggests that many molecules of the enzyme in direct electron contact with the graphite electrode are not catalytically active in a redox state corresponding to the AR form of the enzyme [27,46,47]. Therefore, the AR form can be activated for O 2 catalysis, at low potential for the Cu sites that form the TNC.…”
Section: Electrochemical Characterizationmentioning
confidence: 99%
“…For the first scan ( Figure 1A, black line) the voltammogram on the forward sweep is characterized by two hysteresis observed at~0.40 V and~0.1 V vs SCE, indicating an activation step at low potentials for the ORR. During the second scan the onset for O 2 reduction occurs at~0.5 V. The hysteresis obtained during the first scan suggests that many molecules of the enzyme in direct electron contact with the graphite electrode are not catalytically active in a redox state corresponding to the AR form of the enzyme [27,46,47]. Therefore, the AR form can be activated for O 2 catalysis, at low potential for the Cu sites that form the TNC.…”
Section: Electrochemical Characterizationmentioning
confidence: 99%
“…As an illustration, recent works in our laboratory showed that the half life of a BOD-based bioelectrode incorporated in carbon felts was restricted to one week at room temperature 12 . Furthermore, for direct wiring of a redox enzyme on a conductive support, it is mandatory to allow an electron tunneling between the enzyme active site and the electrode, and to permit substrate access [13][14][15][16][17] . By varying the pH of BOD adsorption on a carbon nanotube (CNT) network, Mazurenko et al demonstrated that electrostatic interactions were driving the adsorption process in an orientation favoring either this direct wiring (direct electron transfer, DET), or a connection via a diffusing redox mediator (MET) 15 .…”
Section: Introductionmentioning
confidence: 99%
“…To obtain an efficient direct electron transfer, the orientation of BOD needs to be controlled in such a way that the active center T1 is close to the electrode surface . In the last decades, numerous strategies have been proposed to immobilize BOD on various electrodes allowing efficient DET . To name a few, DET was achieved by BOD adsorption on electrodes functionalized with carboxyl groups, or by pulse‐assisted techniques .…”
Section: Introductionmentioning
confidence: 99%